Enzyme Catalyzed Synthesis of Fatty Monoethanolamides from Palm Kernel Oil Fractions - Yap, Chiew Lin (1998)
Fatty monoethanolamldes were synthesized In organic solvent from palm kernel olein (PKL) and palm kernel steann (PKS) using a lipase from Candida rugosa The transamldatlon reactions of PKL and PKS were enhanced In the presence of lipase Fatty monoethanolamldes were characterized by melting point, spectroscopic (Infrared red and nuclear magnetic resonance) and gas chromatography The optimal Yield was achieved at reaction time 72 hours for both systems With PKL and PKS as the substrates For PKL as the substrates, the optimal reaction temperature was 40°C, whereas With PKS as the substrate no optimum temperature was found (In the range of temperature studied) where the relative Yield Increased With the Increasing temperature It suggested that the temperature effect on the transamidation of PKS was more significant compared to the transamidation for PKL In both systems the precipitation of high meltin g point fatty monoethanolamides hindered the progress of reactions. Lipase functioned better in hydrophobic sol vents compared to hydrophilic solvents. The best solvent for the reactions was isooctane. The increasing amount of monoethanolamine used also resulted in the increase solubility of the reactants and products, hence, increase the yield. For PKL, increasing the mole ratio of PKL : monoethanolamine to 1:15 increased the relative yield to 4.45-fol d than the relative yield of that PKL : monoethanolamin e at mole ratio 1:1. However for PKS , its relative yield was only 2.5-fold more than the relative yield of that PKS : monoethanolamine at mole ratio 1:1. The optimal ratio of enzyme/PKL (or PKS) was 0.035. An excess of enzyme caused mass transfer limitation. In the water activity studies, the preequilibrium and the direct salt hydrate addition methods were used. Both observations were not in agreement and did not show the actual effects of water activity in transamidation reactions. The enzymes tend to aggregate and did not fully express its function. Th e addition of support hardly improved the conditions. Overall, PKL always showed the higher relative yield compared to PKS . At the optimum conditions, the yield of PKL monoethanolamide was 77.64% and the yield of PKS monoethanolamide was 39.32%. Kinetic studies also sh owed a cl ear preference to PKL which its Km value 10-fold lower than that of PKS at room temperature.